All or nothing? attachment avoidance and the curvilinear effects of partner support. [article]. - Girme, Yuthika U.; Overall, Nickola C.; Simpson, Jeffry A.
People high in attachment avoidance typically respond more negatively to partner support, but some research suggests they can be calmed by high levels of practical support. In the present research, we attempted to reconcile these inconsistencies by modeling curvilinear associations between romantic partners? support and support recipients? outcomes and testing whether these curvilinear associations were moderated by recipients? degree of attachment avoidance. We examined the effect of partner support during support-relevant discussions (Studies 1-3) and in daily life (Study 4) on support recipients? distress (Studies 1-4), self-efficacy (Studies 2 and 3), perceived partner control/criticism (Studies 2 and 4), and distancing from the partner (Study 4). The results and a meta analysis across all four studies (N=298 couples) demonstrated that the curvilinear effect of practical support on recipients? outcomes was moderated by attachment avoidance. Highly avoidant recipients exhibited more negative responses as their partner provided them low-to-moderate levels of practical support, including increasing distress, perceived partner control/criticism and distancing, and decreasing self-efficacy. However, as partner?s practical support shifted from moderate to high levels, highly avoidant recipients experienced more positive outcomes, including decreasing distress, perceived partner control/criticism and distancing, and increasing self-efficacy. Less avoidant individuals were resilient and experienced better outcomes regardless of the level of partner support they received. These results demonstrate the utility of curvilinear models in reconciling the costs and benefits of support, and indicate that high levels of practical support can overcome the defenses of highly avoidant individuals by offering undeniable evidence of the partner?s availability. - - (from the authors)